HIPERALITAS SIMULAKRA DALAM ENDORESMENT DI MEDIA SOSIAL : (Studi Kasus akun Instagram @fadiljaidi) - Lisa, Lisa Sangadah Wardani; Hani, Hani Nur Afiyah; Yulia, Yulia Nurul Hikmah; Faizah, Siti Nur Faizah (Jurnal SUARGA: Studi Keberagamaan dan Keberagaman, 2023)
Social media is an online page for expressing yourself nowadays. Instagram is one of them, the features offered by Instagram make it easy to update daily activities. Instagram gave birth to celebrities who are influential in disseminating information through their uploads. In this research which uses qualitative methods and the simulacra hyperreality approach according to Jean Baudrillard, the results show that the endorser's role in carrying out this endorsement has an influence on the reality of life and religious practices. This condition needs to be re-examined critically, especially regarding the endorsement of Muslim women's products by male endorsers.